Principles Of Fair Work With Children With Disabilities (Zien Journal of Social Sciences and Humanities, 2025)
This study examines the critical issues involved in organizing inclusive education in schools. It outlines the challenges related to teacher training, curriculum adaptation, and resource allocation that hinder the effective integration of students with diverse needs. By analyzing current theoretical frameworks and reviewing key literature, the research identifies the importance of collaborative stakeholder engagement and the integration of modern technological tools in fostering an inclusive educational environment. The paper also discusses the necessity of policy reforms and continuous professional development to support educators and administrators. Practical recommendations are provided to address current shortcomings and to guide future strategies for inclusive education. Ultimately, the study emphasizes that a systematic, research-based approach is essential for creating equitable learning opportunities for all students